The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12889-019-7581-8
|View full text |Cite
|
Sign up to set email alerts
|

Does sexual behaviour of people with HIV reflect antiretroviral therapy as a preventive strategy? A cross-sectional study among outpatients in Kenya

Abstract: Background The World Health Organisation (WHO) advocates early initiation of HIV treatment as a prevention strategy among people living with HIV. There is strong evidence for the effectiveness of antiretroviral therapy (ART) as a preventive tool for HIV transmission. We aimed to determine the sexual behaviour of HIV outpatients and assess if it reflects the current preventive strategy for HIV transmission. Methods We conducted a cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Reports on the sexual behaviors of individuals on HIV treatment in Africa have indicated that individuals on treatment (ART) are more likely to have unprotected sex compared to those who are not on treatment (7,8). Although ART is increasing globally, the impact of ART on sexual risk behavior and transmission of HIV in Africa is still unknown (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports on the sexual behaviors of individuals on HIV treatment in Africa have indicated that individuals on treatment (ART) are more likely to have unprotected sex compared to those who are not on treatment (7,8). Although ART is increasing globally, the impact of ART on sexual risk behavior and transmission of HIV in Africa is still unknown (9).…”
Section: Introductionmentioning
confidence: 99%
“…Although ART may minimize the risk of HIV transmission by persistent viral suppression, therapy may also serve as an excuse for unsafe sexual activities (10). There are several factors, which were reported as contributing factors to the spread of HIV among adults, such as domestic violence, having multiple partners, the practice of unprotected sex, homosexuality, and commercial sex (8,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, others found no difference in sexual risk behaviour, comparing PLHIV on ART and those not on ART [19]. Some studies showed that participants who are not on ART, have more unprotected sexual intercourse than those who are on ART, due to these participants believing that HIV treatment was a sufficient prevention strategy because the risk of transmission is reduced when one is on HIV treatment and viral load has been suppressed [23][24][25]. However, empirical studies have dismissed the increased risk behaviours regarding the perception of reduced HIV transmission risk after ART initiation have largely been dispelled in [9,20,26].…”
Section: Introductionmentioning
confidence: 99%